Experience of observing patients with Duchenne myopathy - L. I. Minaycheva; E. Yu. Petlina; E. G. Ravzhaeva; G. N. Seitova (Русский журнал детской неврологии)
Duchenne muscular dystrophy is a genetically determined fatal disease with a steadily progressive course. It is characterized by the absence or sharp decrease (less than 3 % of the norm) of the dystrophin protein. In recent years, several drugs for pathogenetic treatment of Duchenne myodystrophy have appeared in Russia. Unfortunately, this therapy is not universal and can only be prescribed to patients with certain types and regions of mutations. Establishing an accurate diagnosis for patients will allow timely determination of observation tactics, effective implementation of preventive and rehabilitative measures, and obtaining pathogenetic treatment. Gene therapy is a perspective option. This article describes clinical cases of Duchenne myopathy in patients with different variants of mutations in the dystrophin gene against the background of pathogenetic therapy.